Bonding Characteristics of Single- and Joggled-Lap CFRP Specimens: Mechanical and Acoustic Investigations - Claudia Barile; Caterina Casavola; Vincenzo Moramarco; Carmine Pappalettere; Paramsamy Kannan Vimalathithan (Applied Sciences, 2020)
Two different configurations of adhesive-bonded carbon fiber-reinforced plastic (CFRP) specimens, joggled lap-joint specimens and single lap-joint specimens, are mechanically tested. The mechanical tests show that the joggled lap specimens have lower strength than the single lap specimens. The damage modes in both the specimens are analysed by the Acoustic Emission descriptors recorded during the mechanical tests. The acoustic data as cumulative counts and cumulative energy show the critical points of failure in both the specimen groups under loading. Moreover, they also show that the damage modes in both the specimens are dissimilar. Finally, the data provided by acoustic emission descriptors are verified by fractographic analysis on the failed surface.